2009
DOI: 10.1016/j.ijgo.2009.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Condom use among married women at risk for sexually transmitted infections and HIV in rural China

Abstract: More educational interventions are needed to increase condom knowledge and promotion, especially among less educated women and married women left behind by migrant husbands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
(17 reference statements)
2
10
0
Order By: Relevance
“…Nepalese women have limited access to education, employment, health, decision making and thus they were dependent on husband even for sexual direction. Economic dependency is the major factor which prevents wives to discuss on sexuality, HIV related diseases and HIV prevention 26 which is largely true among migrants' wives in our study. The role of 'power' in sexual relationship was demonstrated in a study on South Asian migrant women in Canada where women with high power in relationship had a high level of knowledge on HIV and they could ask their partner to use a condom.…”
mentioning
confidence: 82%
“…Nepalese women have limited access to education, employment, health, decision making and thus they were dependent on husband even for sexual direction. Economic dependency is the major factor which prevents wives to discuss on sexuality, HIV related diseases and HIV prevention 26 which is largely true among migrants' wives in our study. The role of 'power' in sexual relationship was demonstrated in a study on South Asian migrant women in Canada where women with high power in relationship had a high level of knowledge on HIV and they could ask their partner to use a condom.…”
mentioning
confidence: 82%
“…This is a cross-sectional study conducted in two Percentage effect on the probability of occurrence of the event = (OR-1) x 100 (10) . Therefore, the analysis of the results of the steady partner variable = (0.45-1) x 100= -55%, indicating that the fact that the participant has a steady partner reduced by 55% the likelihood of using a condoms, compared with those without a steady partner, considering that the other independent variables of the model are constant.…”
Section: Methodsmentioning
confidence: 99%
“…Given the above, it is necessary to carry out differentiated work in places that are frequented by heterosexual and homosexual couples, with the aim of developing health education programs. The majority of studies involving the theme of prevention of HIV and other STDs have been developed with convenience samples of specific populations, such as homosexuals (7)(8) , Latin American immigrants living in the USA (9) and Chinese married women (10) .…”
Section: Introductionmentioning
confidence: 99%
“…Chang and her colleagues also found that the rate of having had a sexual experience among youth who had left school was 42.6% (62.3% in males, and 37.7% in females) [22]. Other researchers [23][24][25] have reported higher rates of unsafe sexual behaviors among youth migrants. Most youth migrants work away from their hometown, and they may behave differently that they would in their hometown.…”
Section: Discussionmentioning
confidence: 99%